Incorporation of a Step-Up Boost Converter in Photovoltaic Power Systems for DC Applications. - Imad A. Elzein; Yury N. Petrenko; Mostafa M. Kurdi (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
The dependency of relying on switching power supplies is increasing and in more demand these days to present superior efficiency as it’s compared to conventional linear power supplies. The main target in any type of photovoltaic power system is to increase the efficiency rate of the PV arrays; and as a result power systems that depend on a set of PV arrays have a priority to track the maximum power point MPP to extract the ultimate maximum power from the set of arrays. One of their important characteristics is the ability to provide step-up in the form of Boost converters, step-down in the form of buck converters, and utilized in the sense of inverting. In this research paper we will delineate a sector of the various sort of switching regulators used in dc-dc conversion especially the boost converter. In addition a review of the control techniques for these converters were touched based.